Interferons and HIV Infection: The Good, the Bad, and the Ugly - Netanya Sandler Utay; Daniel C. Douek (Case Western Reserve University, 2016)
Whether type I interferons (IFNs) hinder or facilitate HIV disease progression is controversial. Type I IFNs induce the production of restriction factors that protect against mucosal HIV/SIV acquisition and limit virus replication once systemic infection is established. However, type I IFNs also increase systemic immune activation, a predictor of poor CD4+ T-cell recovery and progression to AIDS, and facilitate production and recruitment of target CD4+ T cells. In addition, type I IFNs induce CD4+ T-cell apoptosis and limit antigen-specific CD4+ and CD8+ T-cell responses. The outcomes of type I IFN signaling may depend on the timing of IFN-stimulated gene upregulation relative to HIV exposure and infection, local versus systemic type I IFN-stimulated gene expression, and the subtype of type I IFN evaluated. To date, most interventional studies have evaluated IFNa2 administration largely in chronic HIV infection, and few have evaluated the effects on tissues or the HIV reservoir. Thus, whether the effect of type I IFN signaling on HIV disease is good, bad, or so complicated as to be ugly remains a topic of hot debate.